In vivo and In vitro Biocompatibility Study of Fe3O4@ZnO and Fe3O4@SiO2 as Photosensitizer for Targeted Breast Cancer Drug Delivery - ehsan naderi; Mahmoud Naseri; Heidar Taimouri Rad; Reza Zolfaghari Emameh; Gholamreza Farnoosh; Ramezan Ali Taheri (Journal of Sciences, Islamic Republic of Iran)
The present study aimed to prepare Fe3O4 nanocarriers (NCs) by a thermal treatment method. After the Fe3O4 (Fe) NCs was prepared, zinc oxide and silica nanoparticles were added to it as Photosensitizer. The structure, morphology, and magnetic properties of Fe3O4@ZnO (Fe@Zn) and Fe3O4@SiO2 (Fe@Si) NCs were determined by XRD, FT-IR, FESEM, and VSM. Then, the loading and drug release of Fe, Fe@Zn, and Fe@Si NCs were investigated. The curcumin (CUR) release of Fe@Zn+CUR and Fe@Si+CUR increased from 30% and 26% at pH 7.4 to 53% and 57% at pH 5.5, respectively. The cytotoxicity of Fe@Zn and Fe@Si NCs were determined by MTT assay, hemolysis test, acute toxicity, and lethal dose test. The results showed that Fe@Zn and Fe@Si were appropriate for Photodynamic Therapy (PDT) and in the next step, the effect of Fe@Zn, Fe@Si, Fe@Zn+CUR, and Fe@Si+CUR NCs on MCF-7 cells under  visible light were studied. Finally, the ranking of the destruction of cancerous cells of MCF-7 using NCs under  visible light was: Fe@Zn+CUR>Fe@Zn>Fe@Si+CUR>Fe@Si.